2020
DOI: 10.4103/jfmpc.jfmpc_1472_20
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle choices and prevalence of chronic noncommunicable diseases among primary healthcare physicians in the Jazan Region, Saudi Arabia

Abstract: Background: One of the factors that may influence patient adherence to a healthy lifestyle is the adherence of their treating physicians to a healthy lifestyle. This study aimed to measure the lifestyles of primary healthcare center (PHCs) physicians in the Jazan region and to identify the prevalence of diabetes, hypertension, hypercholesterolemia, and obesity among this sample of physicians. Methods: This cross-sectional study was conducted in the Jazan region which li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…28 Additionally, an investigation conducted in the Jazan region involving 234 PHC physicians detected a high prevalence of overweight and obese physicians and limited engagement in a healthy lifestyle after measuring their physical activity and dietary habits. 29 Similar observations were noted among healthcare workers in Riyadh in the eastern region of Saudi Arabia, indicating limited engagement in a healthy lifestyle among healthcare workers. 30,31 This highlights the importance of considering the influence of healthcare workers' attitudes toward and adherence to a healthy lifestyle and the possible consequences when providing lifestyle counseling to their patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 55%
“…28 Additionally, an investigation conducted in the Jazan region involving 234 PHC physicians detected a high prevalence of overweight and obese physicians and limited engagement in a healthy lifestyle after measuring their physical activity and dietary habits. 29 Similar observations were noted among healthcare workers in Riyadh in the eastern region of Saudi Arabia, indicating limited engagement in a healthy lifestyle among healthcare workers. 30,31 This highlights the importance of considering the influence of healthcare workers' attitudes toward and adherence to a healthy lifestyle and the possible consequences when providing lifestyle counseling to their patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 55%
“…Table 1 is reproduced from publication by Gosadi et al . [ 12 ] The median age of the physicians was 38 years and the proportions of male and female physicians were similar. The majority of recruited physicians were Sudanese (55%), followed by Saudi physicians (12%).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, previous studies showed that 63.2% of physicians at 3 PHC centers of National Guard Health Affairs in Jeddah were overweight and obese, with similar chronic diseases (Alshareef et al, 2019) as found in our study. A study involving 234 physicians in the Jazan region, Saudi Arabia, similarly found that the majority (70%) were obese and overweight and exercised at low intensity (Gosadi et al, 2020). Though similar chronic diseases were reported among physicians in Bahrain, overweight and obesity presented among 72.5% of Bahraini physicians (Borgan et al, 2015).…”
Section: Discussionmentioning
confidence: 85%